The Effect of Foreign Country Indexes, Macroeconomics, and Commodities on the Indonesian Stock Exchange - Valentino Budhidharma; Roy Sembel; Gracia Shinta S. Ugut; Edison Hulu (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
The purpose of this paper is to study the effect of the foreign country indexes, macroeconomics, and world commodity prices on the Composite Stock Price Index (IHSG) in Indonesia. The foreign indexes are the US Dow Jones (DJI), the Singapore Straits Time Index (STI), the Japanese Nikkei (N225), and the Hong Kong Hang Seng Index (HSI). The macroeconomics factors are the currency exchange rate (USDIDR) and inflation rate (INFLATION). The commodities are crude oil prices (OIL) and world gold prices (GOLD). The estimation model is a multiple linear regression analysis[VB1]Â . The results show that USDIDR has a significant negative effect, while STI has a significant positive effect.